Comparison of the effectiveness of single-dose levofloxacin with single-dose fosfomycin pre-urodynamic study related to the incidence of urinary tract infection: a randomized controlled trial - Harrina Erlianti Rahardjo; Fina Widia; Cindy Wijaya; Kevin Leonardo; Alfred Tanjung; Muhammad Hanif Arfiananda; Fatimah Nuwwaaridya Fitriani; Rahmat Aidil Fajar Siregar; Andika Afriansyah (BMC Urology)
Abstract Purpose The purpose of this study is to examine the efficacy of 500 mg levofloxacin and 3 g fosfomycin given as single-dose prophylactic antibiotics one hour before urodynamic studies (UDS) to prevent urinary tract infections (UTIs). Methods This single-blinded, randomized clinical trial included 126 patients who underwent UDS between December 2022 and March 2024 at two urology centers in Jakarta. The patients, aged 18 years and older, were randomized equally into two groups receiving either 500 mg levofloxacin or 3 g fosfomycin prior to UDS. The primary indications for UDS included lower urinary tract symptoms (LUTS) (54.8%), overactive bladder (OAB) (32.8%), underactive bladder (8.9%), and stress urinary incontinence (3.5%). Three days post-UDS, patients were followed up with urinalysis and clinical assessment for UTI symptoms. Results Among the 126 patients, UTI was diagnosed in 26 cases (20.9%), with 14 cases (22.2%) in the levofloxacin group and 12 cases (19%) in the fosfomycin group, showing no significant difference (p = 0.660). Symptomatic UTIs occurred in 6 patients (4.8%) in the levofloxacin group and 7 patients (5.6%) in the fosfomycin group. E. coli was the most commonly detected bacterium in urine cultures. Conclusion In our center, there was no significant difference in the clinical outcome between the administration of 3 g fosfomycin and 500 mg levofloxacin as single-dose prophylactic antibiotics prior to UDS. Given the rising antibiotic resistance, fosfomycin may be considered an alternative. Further multicenter and multinational studies are warranted, as bacterial profiles and antibiotic resistance patterns may vary across different regions and healthcare systems. Trial registration NCT06017479. Study Registration Date 2023-08-24.